If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + 10)(3x + -1)(3x + 1) = 0 Reorder the terms: (10 + x)(3x + -1)(3x + 1) = 0 Reorder the terms: (10 + x)(-1 + 3x)(3x + 1) = 0 Reorder the terms: (10 + x)(-1 + 3x)(1 + 3x) = 0 Multiply (10 + x) * (-1 + 3x) (10(-1 + 3x) + x(-1 + 3x))(1 + 3x) = 0 ((-1 * 10 + 3x * 10) + x(-1 + 3x))(1 + 3x) = 0 ((-10 + 30x) + x(-1 + 3x))(1 + 3x) = 0 (-10 + 30x + (-1 * x + 3x * x))(1 + 3x) = 0 (-10 + 30x + (-1x + 3x2))(1 + 3x) = 0 Combine like terms: 30x + -1x = 29x (-10 + 29x + 3x2)(1 + 3x) = 0 Multiply (-10 + 29x + 3x2) * (1 + 3x) (-10(1 + 3x) + 29x * (1 + 3x) + 3x2 * (1 + 3x)) = 0 ((1 * -10 + 3x * -10) + 29x * (1 + 3x) + 3x2 * (1 + 3x)) = 0 ((-10 + -30x) + 29x * (1 + 3x) + 3x2 * (1 + 3x)) = 0 (-10 + -30x + (1 * 29x + 3x * 29x) + 3x2 * (1 + 3x)) = 0 (-10 + -30x + (29x + 87x2) + 3x2 * (1 + 3x)) = 0 (-10 + -30x + 29x + 87x2 + (1 * 3x2 + 3x * 3x2)) = 0 (-10 + -30x + 29x + 87x2 + (3x2 + 9x3)) = 0 Combine like terms: -30x + 29x = -1x (-10 + -1x + 87x2 + 3x2 + 9x3) = 0 Combine like terms: 87x2 + 3x2 = 90x2 (-10 + -1x + 90x2 + 9x3) = 0 Solving -10 + -1x + 90x2 + 9x3 = 0 Solving for variable 'x'. The solution to this equation could not be determined.
| s^2-49=0 | | 30a^2+19at-63t^2=0 | | 7-5X=X^2 | | 5x+(10x-125)=1000 | | 5x+3=7x-2 | | -9y=-162 | | (e-9)(e+4)(e-4)=0 | | 6d^2+20d-16=0 | | 3x-1.1=0.7 | | 12w^2-13w-35=0 | | (x+4)(x^3-2x+6)= | | 7p(11p-2)(11p+2)=0 | | 14x^8-15x^6+15x^5= | | 24.1=x(x) | | 0.6x=-60 | | 153+(-17)=-9x+x | | -13=-5-6n+11 | | (x+3)(x^3-2x+6)= | | 3(5x-2)-23=11x+3 | | 5x+(125-x)=1000 | | 9y-3(y+4)=8 | | 28r^2+35ry-4xr-5xy=0 | | 5x+125-x=1000 | | .5x-.3(5-x)=2.9 | | 125x=25 | | 6x=2(7x+16) | | 4(x+2x)=10 | | 2x-8(8-x)=3 | | 8-10x=104-31x | | (x+3)(x^3-6x+5)= | | y=3x^4-13x^3+13x^2-39x+112 | | 13(13)+7x(7x)=y(y) |